Cement system suitable for ultra-deep well cementation and preparation method thereof
By using a mixture of quartz sand and nanosilicon dioxide in the ultra-deep well cementing cement system and a reinforcement made of strength-stabilizing materials A, B and crystal-form-induced materials, combined with high-temperature stabilizers and dispersants, the problem of strength decay of cement stone in ultra-high temperature environment is solved, and the high-temperature compressive strength and high-temperature resistance of cement stone is improved, and the construction requirements of ultra-deep well cementing projects are met.
Patent Information
- Application Number
- CN202411876627.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-19
AI Technical Summary
The prior art cannot effectively prevent the strength of cement stone from declining under ultra-high temperature environments, and cannot meet the construction requirements of ultra-deep well cementing projects.
A cement system suitable for ultra-deep well cementing is adopted, including G-level oil well cement, the first reinforcement material (a mixture of quartz sand and nanosilicon dioxide), the second reinforcement material (composed of mixing strength-stabilizing material A, strength-stabilizing material B and crystal-form-induced material), high-temperature stabilizers and dispersants. Through the synergistic action of these components, the formation of low-calcium-silicon specific hydration products is controlled and the high-temperature resistance of cement stone is improved.
It effectively alleviates the problem of strength decline in cement stone under high temperature conditions, improves the compressive strength and high temperature resistance of cement stone, meets the construction requirements of ultra-deep well cementing projects, and is characterized by green and environmentally friendly and low-cost.
Smart Images

Figure BDA0005197049120000071 
Figure BDA0005197049120000081 
Figure BDA0005197049120000082
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of cementing materials for oil and gas field development, and in particular to a cement system suitable for ultra-deep well cementing and a preparation method thereof. Background Art
[0002] With the development of drilling technology and the deepening of oil field exploration and development, the depth of exploration wells and production wells has been increasing, and deep wells are facing the challenges of being deep, multiple, long and high. However, conventional silicate cement paste will experience strength decline when the curing temperature is around 110°C. At present, it is a common practice to add 30-40% silica sand to cement to reduce the calcium-silicon ratio, thereby improving the strength decline of cement paste. However, when the temperature exceeds 150°C, cement doped with silica sand will still experience strength decline, which can be alleviated by further controlling the amount of silica sand added and the particle fineness. However, as the depth of the well increases, the temperature of deep wells and ultra-deep wells is also getting higher and higher. The existing sand adding system can no longer meet the construction requirements. Therefore, ensuring the long-term strength stability of cement paste in ultra-high temperature environments (>230°C) is still an urgent problem to be solved in cementing engineering.
[0003] Application No. 202111107790.X discloses a high-temperature strength-decay-resistant oil well cement and its preparation method and application. The raw materials, calculated by weight, include the following components: 100.0 parts of oil well cement, 30.0-50.0 parts of quartz sand, 10.0-20.0 parts of high-temperature strength-decay-resistant inhibitor, 3.0-5.0 parts of whisker material, 0.5-2.0 parts of modified carbon nanotubes, 1.0-3.0 parts of dispersant, 2-4 parts of high-temperature stabilizer, 1.0-3.0 parts of high-temperature fluid loss reducer, 3.0-5.0 parts of high-temperature retarder and 65.0-75.0 parts of water.
[0004] Application No. 201810991040.5 discloses a cementing cement for high-temperature deep wells and its preparation method and application. The cementing cement comprises the following components in parts by weight: 100 parts of oil well cement, 30-60 parts of anti-strength decay agent, 10-20 parts of anti-strength decay aid and 5-15 parts of high-temperature enhancer; wherein the anti-strength decay agent is one or two of silicon powder and microsilicon; the anti-strength decay aid is one or more of kaolin, zeolite, wollastonite and diatomite; the high-temperature enhancer is selected from one or more of nano-bentonite, nano-TiO2 and nano-Fe2O3.
[0005] The cement slurry system in the above-mentioned prior art still cannot meet the requirements of ultra-high temperature cementing cement stone to inhibit long-term strength decline, and there is still a lack of effective countermeasures. Therefore, a cement system suitable for ultra-deep well cementing and a preparation method thereof are provided to prevent the strength decline of cement stone in high temperature and ultra-high temperature environments, which has very important practical significance and value for extending the life of oil wells. Summary of the invention
[0006] In order to overcome the defects and shortcomings of the above-mentioned prior art, the present invention provides a cement system suitable for ultra-deep well cementing and a preparation method thereof. The cement system suitable for ultra-deep well cementing of the present invention has the advantages of high temperature strength decay resistance and stable high temperature performance, can effectively alleviate the strength decay problem of cement stone under high temperature conditions, and meet the requirements of oil and gas well cementing.
[0007] To achieve the above object, the technical solution adopted in the present invention is as follows:
[0008] In one aspect, the present invention provides a cement system suitable for ultra-deep well cementing, comprising the following components in weight percentage:
[0009] G-grade oil well cement: 51-68wt%;
[0010] First reinforcement material: 10-15wt%;
[0011] Second reinforcement material: 20-30wt%;
[0012] High temperature stabilizer: 1-2wt%;
[0013] Dispersant: 1-2 wt%;
[0014] The first reinforcing material is formed by mixing quartz sand and nano silicon dioxide in a mass ratio of 15:1.
[0015] The main components of the first reinforcing material of the present invention are crystalline silicon dioxide (quartz sand) and amorphous silicon dioxide (nano silicon dioxide). The combination of the two silicon dioxides can control the formation of hydration products with a low calcium-silicon ratio in the system.
[0016] Furthermore, the SiO2 content of the quartz sand is ≥95wt%, and the powder particle size is 45-90μm.
[0017] Furthermore, the purity of the nano-silicon dioxide is greater than 99wt%.
[0018] Furthermore, the second reinforcing material is prepared by mixing the strength stabilizing material A, the strength stabilizing material B and the crystal inducing material in a mass ratio of (14-16):(1-2):(3-4), and the preparation method is as follows:
[0019] S11, mixing the strength stabilizing material A and the crystal inducing material and placing them in a sealed stirring tank, using anhydrous ethanol as a solvent with a liquid-to-solid ratio of 5:1, stirring at room temperature for 48 hours to form slurry A;
[0020] S12, performing solid-liquid separation and drying on slurry A to obtain powder A;
[0021] S13, mixing the powder A and the strength stabilizing material B uniformly, preferably by a pneumatic mixing device, to obtain a second reinforcing material.
[0022] The second reinforcing material of the present invention adopts solid waste whose main components are SiO2 and Al2O3, which ensures the calcium-silicon ratio and high-temperature strength of the cement slurry system and greatly reduces the use of silica sand.
[0023] Furthermore, the strength stabilizing material A is formed by mixing waste siliceous shale, biomass slag and coal gasification slag in a mass ratio of 2:1:1;
[0024] Preferably, the SiO2 content of the waste siliceous shale is ≥85wt%, and the waste siliceous shale is crushed and ground to form a powder with a particle size of 600 mesh;
[0025] Preferably, the SiO2 content of the biomass slag is ≥65wt%, the Al2O3 content is ≥15wt%, and the biomass slag is dried and ground to form a powder with a particle size of 600 mesh;
[0026] Preferably, the coal gasification slag has a SiO2 content of ≥55wt%, an Al2O3 content of ≥20wt%, a carbon content of ≥10wt%, and a particle size of 375 meshes.
[0027] Furthermore, the strength stabilizing material B is a mixture of nano clay, waste magnesia brick powder and forsterite powder in a mass ratio of 1:1:2;
[0028] Preferably, the SiO2 content of the nanoclay is ≥47wt%, and the Al2O3 content is ≥40wt%;
[0029] Preferably, the MgO content of the waste magnesia brick powder is ≥90wt%, and the powder particle size is 325 mesh;
[0030] Preferably, the forsterite powder has a SiO2 content of ≥40wt%, a MgO content of ≥50wt%, and a powder particle size of <600 mesh.
[0031] Furthermore, the crystal inducing material is waste inorganic insulation material, preferably waste insulation bricks or waste insulation boards;
[0032] More preferably, the components of the insulation brick waste and insulation board waste include xonotlite, tobermorite and silicon dioxide; the insulation brick waste or insulation board waste is crushed into powder, and the powder particle size is less than 10 μm.
[0033] Furthermore, the high temperature stabilizer is a mixture of clay and laponite;
[0034] Preferably, the clay is one or both of chlorite and allophane.
[0035] Furthermore, the dispersant is an aldehyde-ketone condensate.
[0036] The strength stabilizing material B of the present invention and the strength stabilizing material A jointly reduce the calcium-silicon ratio of the cement system, and can also form Mg(OH)2 during the high-temperature hydration process of cement, so that the cement stone has a certain expansibility; in addition, the filling and heterogeneous nucleation effect of nano-clay can refine the pore structure and reduce the porosity, and the synergistic effect with the forsterite powder with excellent temperature resistance greatly reduces the permeability of the cement stone, enhances the density and interface bonding ability of the cement stone, and thus improves the anti-channeling ability and mechanical properties of the cement stone.
[0037] The crystal inducing material of the present invention can be used as a seed material in the cement hydration process to induce the cement hydration product to quickly crystallize at high temperature to form more xonotlite and tobermorite, thereby improving the high temperature resistance of cement paste and avoiding the decline of cement paste strength.
[0038] The present invention utilizes the characteristics of strength stabilizing material A being porous and having a large specific surface area, and loads the crystal inducing material inside and on the surface of the pores of strength stabilizing material A. When the cement hydration product reacts with active ions such as silicon and aluminum released by strength stabilizing material A and strength stabilizing material B, due to the presence of the crystal inducing material, not only the formation of xonotlite and tobermorite is greatly accelerated, but also the formation of aluminosilicate minerals and aluminum substitutes can be induced, thereby further enhancing the high temperature resistance of cement stone and avoiding the decline of strength. In addition, a small amount of carbon powder present in strength stabilizing material A can not only synergize with strength stabilizing material B to fill the pores, but also provide crystallization points for the hydration product and promote hydration. According to the principle of synergistic effect, the second reinforcing material has the characteristics of high temperature resistance, suppression of strength decline, reduced permeability, improved anti-channeling, low cost, and green environmental protection.
[0039] On the other hand, the present invention provides a method for preparing a cement system suitable for ultra-deep well cementing, wherein various masses of G-grade oil well cement, a first reinforcing material, a second reinforcing material, a high-temperature stabilizer and a dispersant are uniformly mixed to obtain a cement system suitable for ultra-deep well cementing.
[0040] Compared with the prior art, the present invention has the following beneficial effects:
[0041] 1. The cementing cement system of the present invention has excellent engineering performance, good adaptability of admixtures, high high-temperature compressive strength and no decay, and uses a large amount of solid waste as the main raw material, which is green, environmentally friendly and low-cost.
[0042] 2. The first reinforcing material of the present invention controls the formation of low calcium-silicon ratio hydration products of the system by combining crystalline silicon dioxide and amorphous silicon dioxide; wherein nano-silicon dioxide can also cooperate with nano-clay in the second reinforcing material to improve the pore structure and stability of cement stone and enhance the compressive strength of the system. The second reinforcing material is used in conjunction with the first reinforcing material, on the one hand, to ensure the reduction of the calcium-silicon ratio of the cement system and improve the effect of improvement and reinforcement; on the other hand, the second reinforcing material forms a large number of active silicon and aluminum groups through dissociation, which can participate in hydration together with the first reinforcing material, and while regulating the formation of low calcium-silicon ratio hydration products, the active aluminum ions in the second reinforcing material can also promote the formation of temperature-resistant aluminosilicate minerals, and further improve the strength and temperature resistance of the cement system under the synergistic effect of the two. DETAILED DESCRIPTION
[0043] In order to make the purpose, technical solutions and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention. In addition, the terms "first", "second", etc. are only used for descriptive purposes and cannot be understood as indicating or implying relative importance.
[0044] The following examples are all prepared according to GB / T19139 standard cement slurry, wherein G-grade oil well cement is provided by Jiahua Special Cement Co., Ltd., the high temperature retarder is diethylenetriamine penta methylene phosphonic acid organic acid, and the high temperature fluid loss reducer is 2-acrylamide-2-methylpropane sulfonic acid polymer. Unless otherwise specified in the examples, all percentages are weight percentages.
[0045] Example 1
[0046] As a preferred embodiment of the present invention, a cement system suitable for ultra-deep well cementing is provided in this embodiment, and the specific components are shown in Table 1 below:
[0047] Table 1
[0048] Components Weight ratio (%) G-grade oil well cement 51 First reinforcement material 15 Second reinforcement material 30 High temperature stabilizer 2 Dispersants 2
[0049] The first reinforcing material of this embodiment is a mixture of quartz sand and nano-silicon dioxide in a mass ratio of 15:1.
[0050] The second reinforcing material of this embodiment is formed by mixing strength stabilizing material A, strength stabilizing material B and crystal inducing material in a mass ratio of 7:1:2.
[0051] According to Table 1, various masses of G-grade oil well cement, the first reinforcing material, the second reinforcing material, the high temperature stabilizer and the dispersant are uniformly mixed to obtain a cement system 1# suitable for ultra-deep well cementing.
[0052] Example 2
[0053] As a preferred embodiment of the present invention, a cement system suitable for ultra-deep well cementing is provided in this embodiment, and the specific components are shown in Table 2 below:
[0054] Table 2
[0055] Components Weight ratio (%) G-grade oil well cement 58.5 First reinforcement material 12.5 Second reinforcement material 25 High temperature stabilizer 2 Dispersants 2
[0056] The first reinforcing material of this embodiment is a mixture of quartz sand and nano-silicon dioxide in a mass ratio of 15:1.
[0057] The second reinforcing material of this embodiment is formed by mixing strength stabilizing material A, strength stabilizing material B and crystal inducing material in a mass ratio of 7:1:2.
[0058] According to Table 2, various masses of G-grade oil well cement, the first reinforcing material, the second reinforcing material, the high temperature stabilizer and the dispersant are uniformly mixed to obtain a cement system 2# suitable for ultra-deep well cementing.
[0059] Example 3
[0060] As a preferred embodiment of the present invention, a cement system suitable for ultra-deep well cementing is provided in this embodiment, and the specific components are shown in Table 3 below:
[0061] Table 3
[0062] Components Weight ratio (%) G-grade oil well cement 66 First reinforcement material 10 Second reinforcement material 20 High temperature stabilizer 2 Dispersants 2
[0063] The first reinforcing material of this embodiment is a mixture of quartz sand and nano-silicon dioxide in a mass ratio of 15:1.
[0064] The second reinforcing material of this embodiment is formed by mixing strength stabilizing material A, strength stabilizing material B and crystal inducing material in a mass ratio of 7:1:2.
[0065] According to Table 3, various masses of G-grade oil well cement, the first reinforcing material, the second reinforcing material, the high temperature stabilizer and the dispersant are uniformly mixed to obtain cement system 3# suitable for ultra-deep well cementing.
[0066] Example 4
[0067] As a preferred embodiment of the present invention, a cement system suitable for ultra-deep well cementing is provided in this embodiment, and the specific components are shown in Table 4 below:
[0068] Table 4
[0069] Components Weight ratio (%) G-grade oil well cement 67 First reinforcement material 10 Second reinforcement material 20 High temperature stabilizer 1 Dispersants 2
[0070] The first reinforcing material of this embodiment is a mixture of quartz sand and nano-silicon dioxide in a mass ratio of 15:1.
[0071] The second reinforcing material of this embodiment is formed by mixing strength stabilizing material A, strength stabilizing material B and crystal inducing material in a mass ratio of 15:2:3.
[0072] According to Table 4, various masses of G-grade oil well cement, the first reinforcing material, the second reinforcing material, the high temperature stabilizer and the dispersant are uniformly mixed to obtain a cement system 4# suitable for ultra-deep well cementing.
[0073] Example 5
[0074] As a preferred embodiment of the present invention, a cement system suitable for ultra-deep well cementing is provided in this embodiment, and the specific components are shown in Table 5 below:
[0075] Table 5
[0076]
[0077]
[0078] The first reinforcing material of this embodiment is a mixture of quartz sand and nano-silicon dioxide in a mass ratio of 15:1.
[0079] The second reinforcing material of this embodiment is formed by mixing strength stabilizing material A, strength stabilizing material B and crystal inducing material in a mass ratio of 16:1:3.
[0080] According to Table 5, various masses of G-grade oil well cement, the first reinforcing material, the second reinforcing material, the high temperature stabilizer and the dispersant are uniformly mixed to obtain a cement system 5# suitable for ultra-deep well cementing.
[0081] Comparative Example 1
[0082] This comparative example is conventional high-temperature cementing cement, and its specific components are 61wt% of G-grade oil well cement, 35wt% of quartz sand, 2wt% of high-temperature stabilizer, and 2wt% of dispersant.
[0083] Comparative Example 2
[0084] This comparative example is the same as Example 1, except that the first reinforcing material does not contain nano-silicon dioxide, and a cementing cement system 1* is obtained.
[0085] Comparative Example 3
[0086] This comparative example is the same as Example 1, except that the second reinforcing material does not contain the strength stabilizer material A, and a cementing cement system 2* is obtained.
[0087] Comparative Example 4
[0088] This comparative example is the same as Example 1, except that the second reinforcing material does not contain a crystal inducing material, and a cementing cement system 3* is obtained.
[0089] Test Case
[0090] The cement slurry was prepared according to GB / T19139 standard, with a liquid-to-solid ratio of 0.44. The engineering performance of the cement slurry prepared by the cement system of Example 1 was tested, and the test conditions were 210° C. The preparation formula of the cement slurry and the test results are shown in Table 6.
[0091] Table 6
[0092]
[0093]
[0094] According to the data in Table 6 above, the ultra-deep well cementing cement system provided by the present invention has good compatibility with admixtures (high temperature retarder, high temperature fluid loss reducer), adjustable thickening time, excellent engineering performance, water loss less than 50 ml, and upper and lower density difference less than 0.05 g / cm 3 , which meets the construction requirements in high temperature environment and is conducive to improving the safety of high temperature cementing operations.
[0095] Cement slurry was prepared according to GB / T19139 standard, with a liquid-to-solid ratio of 0.44. Cement slurries prepared from the cement systems of Examples 1 to 5 and Comparative Examples 1 to 4 were poured into a copper mold and then placed in a high-temperature curing kettle for curing to obtain cement paste. The curing temperature was 250°C, and the curing cycles were 2d, 7d, and 28d. The compressive strength and permeability of the cement paste were tested, and the test results are shown in Table 7.
[0096] Table 7
[0097]
[0098] It can be seen from the data in Table 7 that, compared with Comparative Example 1, the cement paste obtained from Examples 1 to 5 has higher compressive strength after being cured for a certain period of time at 250°C, and has no decline phenomenon; the permeability is low and the internal structure density is high. In addition, compared with the results of Comparative Examples 2 to 4, the components in the present invention have a synergistic effect, and the lack of any one of them cannot achieve the expected effect of the present invention.
[0099] It can be seen from the above embodiments that the cement system suitable for ultra-deep well cementing provided by the present invention has good compatibility with admixtures (high-temperature retarders, high-temperature fluid loss reducers), adjustable thickening time, excellent engineering performance, etc., and can also effectively improve the high-temperature strength stability of cement cementing and reduce the permeability, ensuring that the strength of cement stone does not decline under high-temperature environments, and meeting the performance requirements of cement slurry for ultra-deep well cementing projects.
[0100] Finally, it should be noted that the above embodiments are only preferred embodiments of the present invention to illustrate the technical solutions of the present invention, rather than limiting them, and certainly not limiting the patent scope of the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments can still be modified, or some or all of the technical features can be replaced by equivalents. These modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention. In other words, any changes or modifications made to the main design concept and spirit of the present invention that have no substantive significance, and the technical problems they solve are still consistent with the present invention, should be included in the protection scope of the present invention. In addition, the direct or indirect application of the technical solutions of the present invention in other related technical fields is also included in the patent protection scope of the present invention.
Claims
1. A cement system suitable for ultra-deep well cementing and a preparation method thereof, characterized in that: The following components are included in weight percentage: G-grade oil well cement: 51-68wt%; First reinforcement material: 10-15wt%; Second reinforcement material: 20-30wt%; High temperature stabilizer: 1-2wt%; Dispersant: 1-2 wt%; The first reinforcing material is formed by mixing quartz sand and nano silicon dioxide in a mass ratio of 15:
1.
2. A cement system suitable for ultra-deep well cementing according to claim 1, characterized in that: The SiO2 content of the quartz sand is ≥95wt%, and the powder particle size is 45-90μm.
3. The cement system suitable for ultra-deep well cementing according to claim 1, characterized in that: The purity of the nano silicon dioxide is greater than 99wt%.
4. The cement system suitable for ultra-deep well cementing according to claim 1, characterized in that: The second reinforcing material is prepared by mixing a strength stabilizing material A, a strength stabilizing material B and a crystal inducing material in a mass ratio of (14-16):(1-2):(3-4), and the preparation method is as follows: S11, mixing the strength stabilizing material A and the crystal inducing material and placing them in a sealed stirring tank, using anhydrous ethanol as a solvent with a liquid-to-solid ratio of 5:1, stirring at room temperature for 48 hours to form slurry A; S12, separating the slurry A from the solid and liquid, and drying the slurry to obtain powder A; S13, mixing the powder A and the strength stabilizing material B evenly to obtain a second reinforcing material.
5. The cement system suitable for ultra-deep well cementing according to claim 4, characterized in that: The strength stabilizing material A is made by mixing waste siliceous shale, biomass slag and coal gasification slag in a mass ratio of 2:1:1; Preferably, the SiO2 content of the waste siliceous shale is ≥85wt%, and the waste siliceous shale is crushed and ground to form a powder with a particle size of 600 mesh; Preferably, the SiO2 content of the biomass slag is ≥65wt%, the Al2O3 content is ≥15wt%, and the biomass slag is dried and ground to form a powder with a particle size of 600 mesh; Preferably, the coal gasification slag has a SiO2 content of ≥55wt%, an Al2O3 content of ≥20wt%, a carbon content of ≥10wt%, and a particle size of 375 meshes.
6. The cement system suitable for ultra-deep well cementing according to claim 4, characterized in that: The strength stabilizing material B is a mixture of nano clay, waste magnesia brick powder and forsterite powder in a mass ratio of 1:1:2; Preferably, the SiO2 content of the nanoclay is ≥47wt%, and the Al2O3 content is ≥40wt%; Preferably, the MgO content of the waste magnesia brick powder is ≥90wt%, and the powder particle size is 325 mesh; Preferably, the forsterite powder has a SiO2 content of ≥40wt%, a MgO content of ≥50wt%, and a powder particle size of <600 mesh.
7. The cement system suitable for ultra-deep well cementing according to claim 4, characterized in that: The crystal inducing material is waste inorganic thermal insulation material, preferably waste thermal insulation bricks or waste thermal insulation boards; More preferably, the components of the insulation brick waste and insulation board waste include xonotlite, tobermorite and silicon dioxide; the insulation brick waste or insulation board waste is crushed into powder, and the powder particle size is less than 10 μm.
8. The cement system suitable for ultra-deep well cementing according to claim 1, characterized in that: The high temperature stabilizer is a mixture of clay and laponite; Preferably, the clay is one or both of chlorite and allophane.
9. The cement system suitable for ultra-deep well cementing according to claim 1, characterized in that: The dispersant is an aldehyde-ketone condensate.
10. A method for preparing a cement system suitable for ultra-deep well cementing according to any one of claims 1 to 9, characterized in that: The G-grade oil well cement of various masses, the first reinforcing material, the second reinforcing material, the high temperature stabilizer and the dispersant are uniformly mixed to obtain a cement system suitable for ultra-deep well cementing.
Citation Information
Patent Citations
A cementing agent for high-temperature deep wells, its preparation method and application
CN110862245B
A high-temperature strength degradation-inhibiting oil well cement, its preparation method and application
CN113683354B
Well cementation cement for high-temperature deep well, and preparation method and application thereof
CN110862245A
High-temperature strength decline resistant oil well cement slurry system
CN115304317A
Well cementation cement slurry system capable of resisting ultrahigh temperature of 240 DEG C
CN118955029A
Cited By
Nanocomposite ultra-high density cement slurry and method for preparing the same
CN122502150A